PENGARUH PEER EDUCATION TERHADAP MOTIVASI PERSONAL HYGIENE GENETALIA DALAM PENCEGAHAN KANKER SERVIKS PADA WANITA USIA SUBUR - Rini Rahmayanti; Isesreni Isesreni (Malahayati Nursing Journal, 2020)
ABSTRACT : THE EFFECT OF PEER EDUCATION ON PERSONAL MOTIVATION OF HYGIENE GENETALIA IN PREVENTION OF CANCER SERVICES IN CHILDBEARING AGED WOMEN Background : Cervical cancer is one of the cancers that often attacks women and is a dangerous threat to every woman in the world. One of the causes of cervical cancer is poor genetal hygiene, early prevention that can be done is the provision of health education including using peer eduction methods or peer education.Purpose :  to know the effect of peer education on genetalia personal hygiene motivation in the prevention of cervical cancer in women of childbearing age.Methods : This type of research is a pre-experimental research with a One Group Pretest-Posttest design with a sample of 10 Childbearing age women. Data were analyzed by paired t-test.Results  : The results showed the average motivation before being given peer education was 83.50 with a standard deviation of 8,822, the average motivation after being given peer education was 105.00 with a standard deviation of 5,715. There is a noticeable difference in mean values between before and after peer education intervention with p-value = 0,000 (p 0.05.Conclusions : there is an effect of peer education on genetalia personal hygiene motivation in the prevention of cervical cancer in women of childbearing age (WUS). It is expected that health services can facilitate peer education programs among WUS to increase motivation in genetal hygiene for the prevention of genetal diseases. Keywords : Peer education, Motivation, Genitalia hygiene, Childbearing age women INTISARI : PENGARUH PEER EDUCATION TERHADAP MOTIVASI PERSONAL HYGIENE GENETALIA DALAM PENCEGAHAN KANKER SERVIKS PADA WANITA USIA SUBUR Pendahuluan :  Kanker serviks merupakan kanker yang sering menyerang wanita serta menjadi ancaman berbahaya bagi setiap wanita yang ada diseluruh dunia. Salah satu penyebab kanker serviks adalah hygiene genetalia yang buruk, Pencegahan awal yang dapat dilakukan adalah pemberian pendidikan kesehatan diantaranya menggunakan metode peer eduction atau pendidikan sebaya.Tujuan : Diketahuinya pengaruh peer education terhadap motivasi personal hygiene genetalia dalam pencegahan kanker serviks pada wanita usia subur. Metode : Jenis penelitian yang dilakukan adalah pra eksperimental dengan rancangan One Group Pretest-Posttest dengan jumlah sampel 10 WUS. Data dianalisa dengan uji paired t-test.Hasil : Hasil penelitian didapatkan rata-rata motivasi sebelum diberikan peer education adalah 83.50 dengan standar deviasi 8.822, rata-rata motivasi setelah diberikan peer education adalah 105.00 dengan standar deviasi 5.715. Terlihat ada perbedaan nilai mean antara sebelum dan setelah diberikan intervensi peer education dengan p-value = 0,000 (p0.05),Kesimpulan :  Ada pengaruh peer education terhadap motivasi personal hygiene genetalia dalam pencegahan kanker serviks pada wanita usia subur (WUS). Diharapkan pelayanan kesehatan dapat memfasilitasi program peer education dikalangan WUS untuk meningkatkan motivasi dalam hygiene genetalia untuk pencegahan dari penyakit genetalia. Kata Kunci : Peer education, Motivasi, Hygiene genetalia, Wanita Usia Subur